Utility of 2-[(1-chloro-3-oxoprop-1-en-1-yl)amino]-4-(4-methoxyphenyl)-6-oxo-1, 6-dihydropyrimidine-5-carbonitrile for construction of some new heterocyclic systems as antimicrobial agents. Issue 24 (17th December 2021) - El-Gohary, Nasser M.; Ibrahim, Magdy A.; Farouk, Osama
Abstract: The electron deficient substrate; 2-[(1-chloro-3-oxoprop-1-en-1-yl)amino]-4-(4-methoxyphenyl)-6-oxo-1, 6-dihydropyrimidine-5-carbonitrile (1 ) was utilized as building block for construction of some novel heterocyclic rings bearing pyrimidine nucleus. β-Chloroenaldehyde derivative 1 was allowed to react with a diversity of 1, 3- N, N -binucleophilic reagents producing some heterocyclic systems namely triazolo[4, 3- a ]pyrimidine, pyrimido[1, 2- a ]benzimidazole, pyrimido[1, 2- a ]pyrimidine and pyrimido[2, 1- c ][1, 2, 4]triazine. Reaction of β-chloroenaldehyde 1 with some 1, 3- C, N -binucleophiles produced pyridines, pyrido[1, 2- a ]benzimidazole, pyrazolo[3, 4- b ]pyridine and pyrido[2, 3- d ]pyrimidine incorporating pyrimidine moiety through NH linkage. Condensation of β-chloroenaldehyde 1 with some cyclic active methylene compounds namely dimedone and barbituric acid afforded chromen-2-ylaminopyrimidine and pyrano[2, 3- d ]pyrimidine. Moreover, β-chloroenaldehyde 1 reacted with some 1, 4-binucleophiles namely o -phenylenediamine, 1, 6-diaminopyridone, o -aminophenol and o -aminothiophenol leading to benzodiazepine, pyrido[1, 2- b ][1, 2, 4]triazepine, benzoxazepine and benzothiazepine bearing the pyrimidine moiety through NH linkage. The antimicrobial evaluation of the synthesized compounds appeared variable inhibitory effect toward the tested microorganisms. Structures of the new synthesized products were established based on their analytical and spectral data. Graphical Abstract: UF0001